The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3991/ijet.v14i20.11455
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Students’ Generic Skills with the Integration of e-Service Learning Platform

Abstract: Related previous studies have recognized service learning ability to im-prove students’ generic skills during the service learning projects, however strategies for implementing and evaluating the effects of service learning on students’ generic skills in online environment remain limited. Therefore, this study conducted to identify what are the generic skills mentioned in students’ reflections, the differences when the responses compare to stu-dents’ performance in the course, and to analyze students’ percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
3
18
0
1
Order By: Relevance
“…In reality, e-Service Learning with technology rich environment is able to influence students' learning outcomes especially their generic skills. This is proven in study by Yusof et al [5] and Marcus et al [15] as they found out students also gained generic skills such as online collaborative skills, teamwork, global citizen, scholarship and adaptability with the integration of e-Service Learning platform. Thus, proved that hybrid strategy of service learning that combine both face-to face and online delivery can promote students' generic skills.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In reality, e-Service Learning with technology rich environment is able to influence students' learning outcomes especially their generic skills. This is proven in study by Yusof et al [5] and Marcus et al [15] as they found out students also gained generic skills such as online collaborative skills, teamwork, global citizen, scholarship and adaptability with the integration of e-Service Learning platform. Thus, proved that hybrid strategy of service learning that combine both face-to face and online delivery can promote students' generic skills.…”
Section: Discussionmentioning
confidence: 76%
“…A study about students' critical reflection [16], a comparison between online and traditional service learning [14] and success factors of e-Service Learning [3] resulted in one each. -Lawler [3] Case Study Garca-Gutierrez et al [4] -Yusof [5] Mixed Methods Griffin [6] -Nielsen [7] -Shah [8] Case Study Howlett [9] Mixed Methods Helms [10] Saitta [11] Case Study Jia [12] Case Study Gasper-Hulvat [13] -McGorry [14] -Marcus [15] Action research Guthrie and McCracken [16] -Guthrie and McCracken [17] Qualitative Method Salam [18] -Chen [19] -Fry [20] -Ruso [21] Mixed Methods Harris [22] -…”
Section: Resultsmentioning
confidence: 99%
“…Dalam buku teks, materi ajar berperan penting dalam menunjang tercapainya tujuan pembelajaran. Materi ajar adalah sumber utama dalam suatu pembelajaran (Barnes and McCallops 2019), (Marcus et al 2019). Materi ajar memuat pengetahuan, sikap, dan keterampilan yang harus dipelajari oleh siswa sebagai sarana tercapainya indikator yang sudah disusun dalam standar kompetensi dasar (Huda, Syukur, and Siswanto 2020), (Zhdanko 2019), (Moto et al 2018 perlengkapan dan prosedur yang saling mempengaruhi untuk mencapai tujuan pembelajaran.…”
Section: Struktur Materi Ajarunclassified
“…This concept was first introduced to address two perceived needs of society: the need for youth and education reforms (Billig H., 2000). In addition, service-learning activities benefit students' educational excellence, as well as their social and emotional development (Marcus et al, 2019). In order to develop skills and help people in need, students can connect and use prior knowledge at school.…”
Section: Service-learningmentioning
confidence: 99%
“…Students are provided with skills that benefit themselves through social service activities in the community. Service training provides students with advantages in the academic, social and emotional fields (Marcus, Atan, Talib, Latif, & Yusof, 2019). Many previous studies have discussed the effect of service-learning on students' self-development.…”
Section: Introductionmentioning
confidence: 99%